THE SIMPLE ADDITIVE WEIGHTING (SAW) METHOD TO DETERMINE THE RECIPIENT OF THE PATIENT ASSISTANCE FUND - Rifky Noor Ramdhani; Haryati Haryati (Jurnal Inovasi Ilmu Komputer, 2022)
Patients with serious illnesses and economic conditions that are difficult to seek treatment are a common concern that inspires our humanity to help. Currently there are many social foundations that seek to raise funds from the community to help their treatment. However, the problem is, there are so many patients with illnesses and complex economic backgrounds, so this fundraising foundation finds it difficult to set priorities objectively and measurably to avoid mistargeted funds and possible manipulatives. We need a system that can select patients so that the aid funds are channeled to the right people. The Simple Additive Weighting (SAW) method is a method used to find the optimal alternative from a number of alternatives with certain criteria. This research takes a case study at the Wani Amal Foundation, a foundation engaged in raising aid funds to be distributed to patients in need, while the criteria to be assessed are: Type of disease, severity, monthly income, number of dependents, and home ownership status.